Coal fly ash as a sustainable alternative source for rare earth elements and metal-based nanoparticles: Advances, challenges, and perspectives - Lawrence Sawunyama; Patrick T. Ngueagni; Timothy O. Ajiboye; Ashmore Mawire; Damian C. Onwudiwe (Next Research, 2026)

Integrated geological, economic, and risk assessment of underground hydrogen storage - Prakash Purswani; K C Bijay; Hyeonseok Lee; Yun Yang; Uwaila C. Iyare; Lawrence O. Baompong; Shaowen Mao; David Z. Li; Zhidi Wu; Manjeet Chhetri; Siqin Yu; Xiaoyu Zhang; et al. (Fuel, 2026)

Hums in the humus: opportunities and challenges for soil ecoacoustics - Alex F. Taylor; Martin F. Breed; Carlos Abrahams; Amy Annells; Tom Bradfer-Lawrence; Timothy Cavagnaro; Carolyn-Monika Görres; Martin M. Gossner; Craig Liddicoat; Simon Linke; Oliver C. Metcalf; Louise Roberts; et al. (Trends in Ecology & Evolution, 2026)

Variability of airborne microbial communities and associations with organic pollutants in African air particulate matter across land-use types - Egide Kalisa; Donnabella Lacap-Bugler; Matthew Adams; Jiaqi Bi; Antoine Nsabimana; Gabriel Habiyaremye; Glorieuse Uwizeye; Timothy Lawrence; Kevin Lee; Kazuichi Hayakawa; Stephen Pointing; Stephen DJ. Archer (Atmospheric Environment, 2026)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Potential bedrock exposures of Schrödinger impact melt sheet and/or polymict impact breccias within a crater floor fracture system and volcanic vent - David A. Kring; Valentin T. Bickel; Pascal Lee; Amy L. Fagan; Jennifer L. Heldmann; Rick C. Elphic; David J. Lawrence; Timothy J. Parker; Harrison H. Schmitt (Planetary and Space Science, 2025)

Adaptive sampling with PIXL on the Mars Perseverance rover - Peter R. Lawson; Tanya V. Kizovski; Michael M. Tice; Benton C. Clark; Scott J. VanBommel; David R. Thompson; Lawrence A. Wade; Robert W. Denise; Christopher M. Heirwegh; W. Timothy Elam; Mariek E. Schmidt; Yang Liu; et al. (Icarus, 2025)

Environmental Change Drivers Reduce Sapling Layer Diversity in Sugar Maple-Beech Forests of Eastern North America - Michael R. Zarfos; Gregory B. Lawrence; Colin M. Beier; Blair D. Page; Todd C. McDonnell; Timothy J. Sullivan; Mariann T. Garrison-Johnston; Martin Dovciak (Ecosystems, 2024)

Knowledge co-production for identifying indicators and prioritising solutions for food and land system sustainability in Australia - Romy L. Zyngier; Carla L. Archibald; Brett A. Bryan; Haley Lambert; Enayat A. Moallemi; Mark Elliott; Mark Lawrence; Jane Hutchinson; Lauren T. Bennett; Timothy Reeves; Matthew Pryor; Ulrika Lindholm; et al. (Sustainability Science, 2024)
Achieving sustainable Australian food and land systems requires the rapid implementation and scaling up of a broad suite of solutions to meet the Sustainable Development Goals (SDGs). Decision-making frameworks are needed to identify suitable indicators and prioritise solutions at national scales to inform sustainability transitions. Using a knowledge co-production framework, we convened 150 stakeholders from 100 + organisations to identify 18 nationally relevant indicators that aligned with critical SDGs describing a sustainable food and land system for Australia, in addition to 78 key solutions (supply- and demand-side) to enable progress against these indicators. We then asked subject matter experts to code the impact of each solution on each indicator using an adapted interaction mapping method accounting for uncertainty. The solution category ‘Protecting and restoring nature’, which included solutions targeting conservation and restoration, showed the highest potential for capturing synergies and avoiding trade-offs across multiple indicators. This category exhibited 34.6% of total major synergies, supporting the achievement of clean water and sanitation (SDG6), economic growth (SDG12), life under water (SDG14), and life on land (SDG15). The solution category ‘Carbon sequestration’, which included technological and biological carbon dioxide removal solutions, had the highest number of trade-offs with individual sustainability indicators (42.3%), particularly those relating to zero hunger (SDG2), wellbeing (SDG3), SDG6, SDG14, and SDG15. Our framework can be used to inform future research investment, support the prioritisation of solutions for quantitative modelling, and inform discussions with stakeholders and policymakers for transforming national-scale food and land systems in alignment with the SDGs.

Genetic susceptibility to obesity is partly mediated by emotional overeating during adolescence - Shahina Begum; Elanor C. Hinton; Timothy M. Frayling; Zoi Toumpakari; Natalia Lawrence (Appetite, 2023)

Soil biotic and abiotic thresholds in sugar maple and American beech seedling establishment in forests of the northeastern United States - Jordon C. Tourville; Michael R. Zarfos; Gregory B. Lawrence; Todd C. McDonnell; Timothy J. Sullivan; Martin Dovčiak (Plant and Soil, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Contribution of soil bacteria to the atmosphere across biomes - Stephen D.J. Archer; Kevin C. Lee; Tancredi Caruso; Antonio Alcami; Jonathan G. Araya; S. Craig Cary; Don A. Cowan; Claudia Etchebehere; Batdelger Gantsetseg; Benito Gomez-Silva; Sean Hartery; Ian D. Hogg; et al. (Science of The Total Environment, 2023)

Watershed‐scale liming reveals the short‐ and long‐term effects of pH on the forest soil microbiome and carbon cycling - Bhavya Sridhar; Gregory B. Lawrence; Spencer J. Debenport; Timothy J. Fahey; Daniel H. Buckley; Roland C. Wilhelm; Christine L. Goodale (Environmental Microbiology, 2022)
Summary Soil microbial community composition routinely correlates with pH, reflecting both direct pH effects on microbial physiology and long‐term biogeochemical feedbacks. We used two watershed‐scale liming experiments to identify short‐ (2 years) and long‐term (25 years) changes in the structure and function of bacterial and fungal communities in organic horizons (O e and O a ) of acid forest soils. Liming increased soil pH, extractable calcium, and soil carbon stocks, reduced biomass‐specific respiration, and caused major changes in the soil microbiome in the short and long term. More taxa responded to liming in the short term (70%) than in the long term (30%), with most showing consistent directional responses at both sites. The ratio of change in relative abundance between limed and reference sites was twofold higher at the long than the short‐term site, indicating that the effects of liming grew over time. Liming impacts were most pronounced in fungi, as steep declines of dominant ectomycorrhizal fungi ( Cenococcum and Russula ) occurred at both sites. Liming favoured neutrophilic bacteria over acidophilic populations according to estimated environmental pH optima. Collectively, these results demonstrate that a liming‐induced change of one pH unit has an immediate and persistent effect on the structure and function of microbial communities in acid forest soils. The corresponding suppression of respiration indicates that anthropogenic alterations of soil pH, as driven by acid deposition or liming, can affect forest floor C stocks due to pH‐driven shifts in community structure.

Are we any closer to understanding why fish can die after severe exercise? - Peter Elliot Holder; Chris M. Wood; Michael J. Lawrence; Timothy D. Clark; Cory D. Suski; Jean‐Michel Weber; Andy J. Danylchuk; Steven J. Cooke (Fish and Fisheries, 2022)
Post‐exercise mortality (PEM) may occur when fish exercise to exhaustion and are pushed so far beyond their physiological limits that they can no longer sustain life. Although fish exercise to overcome a variety of natural challenges, the phenomenon of PEM is most often observed as the result of interactions between fish and humans. The seminal work of Black (Can J Fish Aquat Sci, 15:573, 1958) and Wood et al. (J Fish Biol, 22:189, 1983) provided a foundation for exploring the potential causes of PEM in fish. With no “silver bullet” explaining PEM being apparent, contemporary research has continued to focus on physiological mechanisms of exhaustion in fish, including factors such as oxygen delivery, ion regulation, hormone signalling, and cardiac function. This paper provides an overview of these studies, and reviews the continuous improvement in data collection methods, tools, and experimental protocols used to examine the PEM phenomenon. These studies of exhaustion have played an important role in informing management actions for activities such as bycatch revival and fish passage. Since the contribution of Wood et al. (Journal of Fish Biology, 22(2):189–201, 1983), the combined efforts of fundamental and applied research have yielded a greater understanding of why fish die after severe exercise, yet much remains to be explored through future work.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Estimating and Applying Fish and Invertebrate Density and Production Enhancement from Seagrass, Salt Marsh Edge, and Oyster Reef Nursery Habitats in the Gulf of Mexico - Philine S. E. zu Ermgassen; Bryan DeAngelis; Jonathan R. Gair; Sophus zu Ermgassen; Ronald Baker; Andre Daniels; Timothy C. MacDonald; Kara Meckley; Sean Powers; Marta Ribera; Lawrence P. Rozas; Jonathan H. Grabowski (Estuaries and Coasts, 2021)
Seagrasses, oyster reefs, and salt marshes are critical coastal habitats that support high densities of juvenile fish and invertebrates. Yet which species are enhanced through these nursery habitats, and to what degree, remains largely unquantified. Densities of young-of-year fish and invertebrates in seagrasses, oyster reefs, and salt marsh edges as well as in paired adjacent unstructured habitats of the northern Gulf of Mexico were compiled. Species consistently found at higher densities in the structured habitats were identified, and species-specific growth and mortality models were applied to derive production enhancement estimates arising from this enhanced density. Enhancement levels for fish and invertebrate production were similar for seagrass (1370 [SD 317] g m –2 y –1 for 25 enhanced species) and salt marsh edge habitats (1222 [SD 190] g m –2 y –1 , 25 spp.), whereas oyster reefs produced ~650 [SD 114] g m –2 y –1 (20 spp). This difference was partly due to lower densities of juvenile blue crab ( Callinectes sapidus ) on oyster reefs, although only oyster reefs enhanced commercially valuable stone crabs ( Menippe spp.). The production estimates were applied to Galveston Bay, Texas, and Pensacola Bay, Florida, for species known to recruit consistently in those embayments. These case studies illustrated variability in production enhancement by coastal habitats within the northern Gulf of Mexico. Quantitative estimates of production enhancement within specific embayments can be used to quantify the role of essential fish habitat, inform management decisions, and communicate the value of habitat protection and restoration.

Muscle from aged rats is resistant to mechanotherapy during atrophy and reloading - Marcus M. Lawrence; Douglas W. Van Pelt; Amy L. Confides; Zachary R. Hettinger; Emily R. Hunt; Justin J. Reid; Jaime L. Laurin; Frederick F. Peelor; Timothy A. Butterfield; Benjamin F. Miller; Esther E. Dupont-Versteegden (GeroScience, 2021)

Best practices for non‐lethal blood sampling of fish via the caudal vasculature - Michael J. Lawrence; Graham D. Raby; Amy K. Teffer; Ken M. Jeffries; Andy J. Danylchuk; Erika J. Eliason; Caleb T. Hasler; Timothy D. Clark; Steven J. Cooke (Journal of Fish Biology, 2020)
Blood sampling through the caudal vasculature is a widely used technique in fish biology for investigating organismal health and physiology. In live fishes, it can provide a quick, easy and relatively non‐invasive method for obtaining a blood sample ( cf . cannulation and cardiac puncture). Here, a general set of recommendations are provided for optimizing the blood sampling protocol that reflects best practices in animal welfare and sample integrity. This includes selecting appropriate use of anaesthetics for blood sampling as well as restraint techniques for situations where sedation is not used. In addition, ideal sampling environments where the fish can freely ventilate and strategies for minimizing handling time are discussed. This study summarizes the techniques used for extracting blood from the caudal vasculature in live fishes, highlighting the phlebotomy itself, the timing of sampling events and acceptable blood sample volumes. This study further discuss considerations for selecting appropriate physiological metrics when sampling in the caudal region and the potential benefits that this technique provides with respect to long‐term biological assessments. Although general guidelines for blood sampling are provided here, it should be recognized that contextual considerations ( e.g. , taxonomic diversity, legal matters, environmental constraints) may influence the approach to blood sampling. Overall, it can be concluded that when done properly, blood sampling live fishes through the caudal vasculature is quick, efficient and minimally invasive, thus promoting conditions where live release of focal animals is possible.

Plant richness and composition in hardwood forest understories vary along an acidic deposition and soil-chemical gradient in the northeastern United States - Michael R. Zarfos; Martin Dovciak; Gregory B. Lawrence; Todd C. McDonnell; Timothy J. Sullivan (Plant and Soil, 2019)

Soil Base Saturation Combines with Beech Bark Disease to Influence Composition and Structure of Sugar Maple-Beech Forests in an Acid Rain-Impacted Region - Gregory B. Lawrence; Todd C. McDonnell; Timothy J. Sullivan; Martin Dovciak; Scott W. Bailey; Michael R. Antidormi; Michael R. Zarfos (Ecosystems, 2018)

Correlations between age, functional status, and the senescence-associated proteins HMGB2 and p16INK4a - Ibiyonu Lawrence; Michael Bene; Timothy Nacarelli; Ashley Azar; Justin Z. Cohen; Claudio Torres; Gregg Johannes; Christian Sell (GeroScience, 2018)

Untapped Potential: Opportunities and Challenges for Sustainable Bioenergy Production from Marginal Lands in the Northeast USA - Cathelijne R. Stoof; Brian K. Richards; Peter B. Woodbury; Eric S. Fabio; Alice R. Brumbach; Jerry Cherney; Srabani Das; Larry Geohring; Julie Hansen; Josh Hornesky; Hilary Mayton; Cedric Mason; et al. (BioEnergy Research, 2015)

A Wave Glider Approach to Fisheries Acoustics: Transforming How We Monitor the Nation's Commercial Fisheries in the 21st Century - Charles Greene; Erin Meyer-Gutbrod; Louise McGarry; Lawrence Hufnagle; Dezhang Chu; Sam McClatchie; Asa Packer; Jae-Byung Jung; Timothy Acker; Huck Dorn; Chris Pelkie (Oceanography, 2014)

Quantitative Analysis of Target Coverage and Germinal Center Response by a CXCL13 Neutralizing Antibody in a T-Dependent Mouse Immunization Model - Joanne Brodfuehrer; Andrew Rankin; Jason Edmonds; Sean Keegan; Tatyana Andreyeva; Rosemary Lawrence-Henderson; Josef Ozer; Huilan Gao; Laird Bloom; Angela Boisvert; Khetemenee Lam; Julie Lee; et al. (Pharmaceutical Research, 2014)

Yield and Woody Biomass Traits of Novel Shrub Willow Hybrids at Two Contrasting Sites - Michelle J. Serapiglia; Kimberly D. Cameron; Arthur J. Stipanovic; Lawrence P. Abrahamson; Timothy A. Volk; Lawrence B. Smart (BioEnergy Research, 2013)

Simulation of Intrathrombus Fluid and Solute Transport Using In Vivo Clot Structures with Single Platelet Resolution - Roman S. Voronov; Timothy J. Stalker; Lawrence F. Brass; Scott L. Diamond (Annals of Biomedical Engineering, 2013)

Root dynamics of Carex stricta-dominated tussock meadows - Beth A. Lawrence; Timothy J. Fahey; Joy B. Zedler (Plant and Soil, 2013)

Advancing Sustainable Bioenergy: Evolving Stakeholder Interests and the Relevance of Research - Timothy Lawrence Johnson; Jeffrey M. Bielicki; Rebecca S. Dodder; Michael R. Hilliard; P. Ozge Kaplan; C. Andrew Miller (Environmental Management, 2013)

Dosing of adult pigeons with as little as one #9 lead pellet caused severe δ-ALAD depression, suggesting potential adverse effects in wild populations - Jeremy P. Holladay; Mandy Nisanian; Susan Williams; R. Cary Tuckfield; Richard Kerr; Timothy Jarrett; Lawrence Tannenbaum; Steven D. Holladay; Ajay Sharma; Robert M. Gogal (Ecotoxicology, 2012)

Oral Lead Bullet Fragment Exposure in Northern Bobwhite (Colinus virginianus) - Richard Kerr; Jeremy Holladay; Steven Holladay; Lawrence Tannenbaum; Barbara Selcer; Blair Meldrum; Susan Williams; Timothy Jarrett; Robert Gogal (Archives of Environmental Contamination and Toxicology, 2011)

Bridge Monitoring and Performance Evaluation - Timothy O. Lawrence; Chad T. Ritter; Janos Gergely (Geotechnical and Geological Engineering, 2011)

Differentially expressed genes during malting and correlation with malting quality phenotypes in barley (Hordeum vulgare L.) - Nora L. V. Lapitan; Ann Hess; Blake Cooper; Anna-Maria Botha; Deborah Badillo; Hari Iyer; Jolanta Menert; Timothy Close; Les Wright; Gary Hanning; M. Tahir; Christopher Lawrence (Theoretical and Applied Genetics, 2009)

Alcohol-induced retrograde memory impairment in rats: prevention by caffeine - Michael J. Spinetta; Martin T. Woodlee; Leila M. Feinberg; Chris Stroud; Kellan Schallert; Lawrence K. Cormack; Timothy Schallert (Psychopharmacology, 2008)

Quantitative Genetics of Traits Indicative of Biomass Production and Heterosis in 34 Full-sib F1 Salix eriocephala Families - Kimberly D. Cameron; Ingrid S. Phillips; Richard F. Kopp; Timothy A. Volk; Charles A. Maynard; Lawrence P. Abrahamson; Lawrence B. Smart (BioEnergy Research, 2008)

Gene transcript and metabolite profiling of elicitor-induced opium poppy cell cultures reveals the coordinate regulation of primary and secondary metabolism - Katherine G. Zulak; Anthony Cornish; Timothy E. Daskalchuk; Michael K. Deyholos; Dayan B. Goodenowe; Paul M. K. Gordon; Darren Klassen; Lawrence E. Pelcher; Christoph W. Sensen; Peter J. Facchini (Planta, 2007)

Retention of a Duplicate Gene Through Changes in Subcellular Targeting: An Electron Transport Protein Homologue Localizes to the Golgi - Timothy R. Schmidt; Jeffrey W. Doan; Morris Goodman; Lawrence I. Grossman (Journal of Molecular Evolution, 2003)

Radiation hybrid mapping of 70 rat genes from a data set of differentially expressed genes - Caroline A. Wallace; Saira Ali; Anne M. Glazier; Penny J. Norsworthy; Danilo C. Carlos; James Scott; Tom C. Freeman; Lawrence W. Stanton; Anne E. Kwitek; Timothy J. Aitman (Mammalian Genome, 2002)

Cloning and expression of human sialic acid pathway genes to generate CMP-sialic acids in insect cells - Shawn M. Lawrence; Kathleen A. Huddleston; Noboru Tomiya; Nam Nguyen; Yuan C. Lee; Willie F. Vann; Timothy A. Coleman; Michael J. Betenbaugh (Glycoconjugate Journal, 2001)

Perceived Ecological Risks to Water Environments from Selected Forest Industry Activities - Nigel Cavanagh; Timothy McDaniels; Lawrence Axelrod; Paul Slovic (Forest Science, 2000)
This article examines underlying factors shaping lay perceptions, and differences between lay and expert perceptions, of the ecological risks to water environments associated with six forest industry activities. A survey was administered to 183 lay subjects in four communities within the Lower Fraser Basin of western Canada. Parts of the survey were also administered to 16 aquatic science professionals. The results show that both lay and expert respondents generally perceive that clearcut logging and effluent from pulp mills pose a high degree of risk, while selective logging poses a lesser degree of risk. Both groups believe that fertilizer use poses a risk to water quality. However, the experts viewed the construction of logging roads as posing significantly more risk to water environments, and requiring greater regulation, than did the lay respondents. Conversely, the lay respondents viewed pesticide use as posing significantly more risk to water environments, and requiring greater regulation, than did the expert respondents. Discussion about the implications of these perceptions in terms of policy issues and communication efforts complete the article. FOR. SCI. 46(3): 344–355.

Understanding the cellular uptake of phosphopeptides - Alban J. Allentoff; Sreekala Mandiyan; Hongbin Liang; Anton Yuryev; Isidoros Vlattas; Timothy Duelfer; Iou-Iou Sytwu; Lawrence P. Wennogle (Cell Biochemistry and Biophysics, 1999)

Water relations of host trees and resistance to the phloem-boring beetle Phoracantha semipunctata F. (Coleoptera: Cerambycidae) - Lawrence M. Hanks; Timothy D. Paine; Jocelyn G. Millar; Christopher D. Campbell; Ursula K. Schuch (Oecologia, 1999)

The 5' region of the COX4 gene contains a novel overlapping gene, NOC4 - Nancy J. Bachman; Wei Wu; Timothy R. Schmidt; Lawrence I. Grossman; Margaret I. Lomax (Mammalian Genome, 1999)